2018
DOI: 10.1001/jamaophthalmol.2018.0244
|View full text |Cite
|
Sign up to set email alerts
|

Association of Social Support Network Size With Receipt of Cataract Surgery in Older Adults

Abstract: IMPORTANCE Cataract-related vision impairment is an important public health issue that tends to affect older adults. Little is known about the association between older adults' social support networks and their likelihood of receiving cataract surgery. OBJECTIVE To determine if older adults with smaller social support networks are less likely to receive cataract surgery. DESIGN, SETTING, AND PARTICIPANTS Retrospective cohort study. The National Health and Aging Trends Study, a nationally representative US surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The NHATS is a nationally representative survey that is administered annually to a cohort of US Medicare beneficiaries 65 years and older and has provided important insights on vision and aging. [5][6][7]21 The baseline NHATS sample was recruited in 2011, and the sample was replenished in 2015. At the time of recruitment, all participants were living in settings other than nursing homes.…”
Section: Study Samplementioning
confidence: 99%
“…The NHATS is a nationally representative survey that is administered annually to a cohort of US Medicare beneficiaries 65 years and older and has provided important insights on vision and aging. [5][6][7]21 The baseline NHATS sample was recruited in 2011, and the sample was replenished in 2015. At the time of recruitment, all participants were living in settings other than nursing homes.…”
Section: Study Samplementioning
confidence: 99%
“…A parsimonious set of demographic, socioeconomic, psychosocial, and illness factors that were known to be associated with both VI and well-being (3,4,9,23,24) were included as covariates. Demographic factors included age groups in 5-year intervals, sex, and race/ethnicity.…”
Section: Covariatesmentioning
confidence: 99%
“…(5) Of note, it has been reported that older adults with dementia are less likely than their peers to undergo cataract surgery. (6) To date, there have been relatively few publications on cataract surgery in patients older than 90 years. (1,2,5,7) Reports on outcome in these very elderly people are conflicting as to whether older age, in itself, is a significant predictor of worse visual acuity outcome or not.…”
Section: Introductionmentioning
confidence: 99%